VHF-PECVD grown silicon nanoneedles: role of substrate temperature - Mohammed, Y.H. (Academic Press, 2016)
Achieving highly aligned and dense silicon (Si) nanoneedles (NNs) is ever demanding for optoelectronics. We report the substrate temperature assisted Au-catalyzed SiNNs synthesis via very high frequency plasma enhanced chemical vapor deposition (VHF-PECVD) technique. The effects of varying substrate temperatures (350-550 °C) on the growth process are examined. The maximum density of SiNNs (∼10 NN/μm2) is obtained at the optimum temperature of 550 °C. These NNs have diameters ranging from 38 to 87 nm and the lengths are extended up to 2.96 ± 0.09 μm. Furthermore, the sample prepared at 350 °C is totally devoid of any SiNNs. The axial NNs growth rate increased from 35.3 ± 2.3 nm/min (at 400 °C) to 138.8 ± 8.9 nm/min (at 550 °C). XRD analysis demonstrated the SiNNs cubic structure with preferred orientation along <111>. The NNs prepared at 550 °C displayed better crystallinity than those obtained at other temperatures. This enhanced crystallinity is further supported by Raman measurements. High resolution transmission electron microscopy (HRTEM) confirmed that these NNs are composed of crystalline Si core with an oxide shell. Sample grown at 400 °C revealed a reflectance of 28.642% in the visible region. However, the highly dense SiNNs grown at 550 °C showed a noticeable suppression in the reflectance (15.787%), indicating excellent anti-reflection attributes. The excellent features of the presented results suggest that our systematic method may constitute a basis for the temperature mediated tunable growth of SiNNs suitable for optoelectronics devices.